Socioeconomic and demographic determinants of familial social capital inequalities: a cross-sectional study of young people in sub-Saharan African context - Evelyn Aboagye Addae (BMC, 2020)
Abstract Background Social capital is broadly acknowledged as a vital 'health asset' that promotes young people's health and wellbeing and has the potential to prevent social- and health-related risk behaviours in the life-course. However, limited research has investigated the determinants of social capital for young people in sub-Saharan Africa. This study examines the role of socioeconomic and demographic factors in establishing inequalities in familial social capital among young people in Ghana. Methods The study utilised a cross-sectional survey data involving 2068 in-school adolescents (13-18 years) in the Upper West Region, Ghana. Familial social capital was assessed by 'family sense of belonging', 'family autonomy support' and 'family control'. Multinomial logistic regressions established the relationships between socioeconomic and demographic factors and the measures of familial social capital. Results Adolescents from low affluence households had about 63 and 61% lower odds of attaining a high family sense of belonging (FSB) (OR = 0.373; 95%CI: 0.27-0.513) and high family autonomy support (FAS) (OR = 0.387; 95%CI: 0.270-0.556) respectively but had 67% higher odds of reporting high family control (FC) (OR = 1.673; 95%CI: 1.187-2.359) than their counterparts. Males had about 55 and 71% higher odds to possess high FSB (OR = 1.549; 95%CI: 1.210-1.983) and high FAS (OR = 1.705; 95%CI: 1.272-2.284) respectively but had 38% lower odds to report high family control (OR = 0.624; 95%CI: 0.474-0.822) than females. The odd of young adolescents to attain high FSB than older adolescents were about 66% higher (OR = 1.662; 95%CI: 1.168-2.367). Religion, educational level, ethnicity, family structure, and marital status were also significant predictors of adolescents' family sense of belonging, family autonomy support and, family control. Conclusions Socioeconomic and demographic factors influence inequalities in the amount of familial social capital possessed by young people which suggests possible risks of social inequality. The family context is possibly failing some cohorts of young people with particular reference to female and poor adolescents regarding familial cognitive social capital. Public health strategies should include families in addressing socioeconomic and demographic differences in social capital with a key focus on the cohorts of young people at risk of social capital inequality.